A multi-layered Fe2O3/graphene composite with mesopores as a catalyst for rechargeable aprotic lithium–oxygen batteries. (1st August 2016) - Feng, Ningning; Mu, Xiaowei; Zheng, Mingbo; Wang, Chaoqiang; Lin, Zixia; Zhang, Xueping; Shi, Yi; He, Ping; Zhou, Haoshen
Abstract: Aprotic Li–O2 batteries have attracted a huge amount of interest in the past decade owing to their extremely high energy density. However, identifying a desirable cathodic catalyst for this promising battery system is one of the biggest challenges at present. In this work, a multi-layered Fe2 O3 /graphene nanosheets (Fe2 O3 /GNS) composite with sandwich structure was synthesized using an easy thermal casting method, and served as a cathodic catalyst for aprotic Li–O2 batteries. The aprotic Li–O2 cell with the Fe2 O3 /GNS catalyst demonstrated a better reversibility, lower overpotential for oxygen evolution, and a higher Coulombic efficiency (close to 100%) than those of pure GNS. An excellent rate performance and good cycle stability were also confirmed. The results, characterized by ex and in situ methods, revealed that the dominant discharge product Li2 O2 was decomposed below 4.35 V. This superior electrochemical performance is mainly attributed to the unique sandwich structure of the Fe2 O3 /GNS catalyst with mesopores, which can provide substantially more catalytic sites and prevent direct contact between carbon and Li2 O2 .